Utilization Of Fermented Lemna sp Leaf Meal With Aspergillus niger As Feed Inggredients To Increase The Growth Of Freshwater Pomfret (Colossoma macropomum) - Ronal P Sianturi; Indra Suharman; Adelina Adelina (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This research was conducted for 56 days to evaluate the utilization of Lemna sp leaf meal fermented using Aspergillus niger on growth and feed efficiency of freshwater pomfret (Colossoma macropomum). The method used in this study is the experimental method using a completely randomized design (CRD) with five treatments and three replications. The tested fish used were C. macropomum with an average weight of 2,3±0,3 g. The test feed used was artificial feed with 30% protein content with substitution percentage of soybean meal (SBM) by fermented Lemna leaf flour (FLLF) namely 0%, 25%, 50%, 75% and 100%. The fish are fed three times a day with ten percent of the total biomass at 07.00, 12.00 and 17.00. The result showed that the use of FLLF had a significantly effected (P<0,05) on growth and feed efficiency. Replacement 75% of Lemna sp fermented produces the highest specific growth rate 3,415, feed efficiency 37,40% and feed digestibility 70,24%.